The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1104/pp.97.2.562
|View full text |Cite
|
Sign up to set email alerts
|

NaCl Regulation of Tonoplast ATPase 70-Kilodalton Subunit mRNA in Tobacco Cells

Abstract: osmotica (3, 11, 14). Because cytosolic physiological and biochemical processes apparently are inhibited by high ion concentrations, mechanisms that permit compartmentation of these ions in the vacuole and regulate the concentrations of these ions in the cytosol are of substantial importance for adaptation and growth (11,14,15 for the uphill transport of ions and other solutes into the vacuole. The A/H. across the tonoplast is produced by electrogenic H+ pumps, the H+-ATPase (22), and the H+ translocating pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 28 publications
2
62
1
1
Order By: Relevance
“…In barley roots, increased H+ transport activity did not peak until3 d after the onset of NaCl treatment, and this induction was inhibited by protein synthesis inhibitors, indicating that de novo synthesis was required. Accordingly, 70-kD subunit (subunit B) mRNA of the vacuolar H+-ATPase accumulated in response to NaCl treatment (Narasimhan et al, 1991). These data imply that salt-induced H+ transport activity of the tonoplast ATPase is mediated through increased gene expression.…”
Section: Sodium Efflux and Vacuolar Compartmentationmentioning
confidence: 58%
“…In barley roots, increased H+ transport activity did not peak until3 d after the onset of NaCl treatment, and this induction was inhibited by protein synthesis inhibitors, indicating that de novo synthesis was required. Accordingly, 70-kD subunit (subunit B) mRNA of the vacuolar H+-ATPase accumulated in response to NaCl treatment (Narasimhan et al, 1991). These data imply that salt-induced H+ transport activity of the tonoplast ATPase is mediated through increased gene expression.…”
Section: Sodium Efflux and Vacuolar Compartmentationmentioning
confidence: 58%
“…A higher specific activity of the V-ATPase was observed in saltadapted compared with unadapted suspension-culture cells of Nicotiana tabacurn (Reuveni et aL, 1990), and was found to be associated with a small growth-phasedependent increase in mRNA levels for the A subunit (Narasimhan et aL, 1991). HSrtensteiner et aL (1994) also detected a slight increase in transcript levels for the B subunit of the V-ATPase caused by salt during growth of evacuolated protoplasts of N. tabacum, but this was concluded to reflect an osmotic effect on the rate of vacuole regeneration.…”
Section: Changes In Mrna Levels For the V-atpase C Subunit In Responsmentioning
confidence: 96%
“…It has been reported that salt treatment of plants induces the activities of the plasma membrane and tonoplast proton pumps (Reuveni et al, 1990;Niu et al, 1993;Perez-Prat et al, 1994;Binzel, 1995;Klobus and Janicka-Russak, 2004). Accumulation of both PM-H + ATPase (Niu et al, 1993;Perez-Prat et al, 1994) and V-H + ATPase (Narasimhan et al, 1991) mRNAs under NaCl-stress and the positive correlation with salt tolerance (Braun et al, 1986;Niu et al, 1993;Perez-Prat et al, 1994) are well studied. In the halophyte Atriplex nummularia Lindl., the proton transport capacity of the PM-H + ATPase has been reported by higher Na + concentration (Niu et al, 1993).…”
Section: Northern Analysis Ofmentioning
confidence: 99%